SISTEM INFORMASI PARIWISATA BERBASIS WEBSITE DI KAWASAN BIRA BULUKUMBA - Amar, Musdalifa; Sulaiman, Husni; Iryani, Juniarti (CV. LAJAGOE PUSTAKA, 2025)
This study aims to: (1) Design a website-based tourism information system in the Bira Bulukumba area. (2) Know the response of a website-based tourism information system in the Bira Bulukumba area. This study uses the four-D (4-D) method with the stages, namely: (1) Define (define). (2) Design (design). (3) Development (development). (4) Disseminate (disseminate). Based on the results of the research that has been conducted, several conclusions can be drawn, namely: (1) Website-based Tourism Information System in the Bira Bulukumba Region is designed using UML (Unified Modeling Language) diagram, (usecase diagram, sequence, and the data-based diagram of a Black-princogram (2) Based on the system validation conducted by 2 expert validators produce a value of 0,8 with a high level of validity, meaning that the system has good quality and attraction. The user response to the system was obtained from a test results resulted in a value of 84%. The user satisfaction rate in the website-based tourism information system in the bisamba area is included in the excellent category.